Interpretasi Bentuk dan Warna pada Tanda Navigasi Maritim: Perspektif Semiotik - Dhion Meitreya Vidhiasi; Ike Nurhayati Effendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2025)
This study seeks to elucidate the significance of marine navigation markings and the implications that may ensue from their infringement. This research is a semiotic analysis that examines the importance of the colors and shapes employed in each navigation marker. This study utilizes secondary data sourced from the IALA Maritime Buoyage System. This study references various regulations established by the International Maritime Organization and the Indonesian government to examine the legal infractions resulting from breaches of maritime navigation markers. The findings of this study demonstrate that marine navigation markers predominantly utilize two shapes: the spherical form, signifying warning and prohibition, and the conical form, indicating direction. Moreover, the utilization of hues such as black, red, yellow, green, and white enhances the connotations of warning, prohibition, and guidance. The IALA Maritime Buoyage System standards do not address breaches or penalties. Negligence in adhering to marine navigation markings may jeopardize the security and safety of shipping, resulting in criminal penalties. This study aims to serve as a reference for comprehending the significance of maritime navigation markings in establishing safe and secure shipping conditions. By doing so, it contributes to a deeper understanding of safety through the human interpretation of symbolic systems at sea.